Strategi Perancangan Manajemen Pelayanan di Kantor Notaris dan PPAT Anita Mahdalena, S.H - Febryna Adinda Syafutri; Renza Fahlevi (Jurnal Publikasi Ilmu Manajemen, 2024)
Facing the increasing demand for notary and PPAT services, an effective management strategy needs to be designed to handle the surge in demand without compromising service quality. The digital era encourages the integration of technology and automation as a solution to enhance efficiency. This research aims to design a service strategy, focusing on improving service quality, effective communication, and refining the notarization process. Services are structured to meet the varied needs of customers, involving aspects of convenience, speed, personal interaction, skills, and friendliness.The Notary Office & PPAT Anita Mahdalena, SH, as a provider of legal services, becomes the object of the study. This program seeks to increase the visibility of the office through the development of an official website, leveraging social media, and strengthening the office's identity. The research methodology involves primary data from interviews and direct observations, as well as secondary data from external sources The research findings indicate that the implementation of the service strategy with the creation of an official website has increased transparency, trust, and information access. The distribution of souvenirs and ID cards helps strengthen positive bonds with customers and enhances security and employee identity. This program has successfully achieved the goal of improving a positive image and establishing long-term relationships with clients.